Art or science? The challenges of publishing peer reviewed papers based on linked models - Alison Burrell (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
The methodology used in a linked model system is generally too voluminous and of insufficient interest to form the basis of a peer-reviewed journal article. To be readily acceptable to an economics journal, the simulation results should provide economic insight and contribute to the economics literature.
Keywords: 330